Pendampingan Agribisnis Anggrek Hibrida di Kecamatan Matesih Kabupaten Karanganyar - Sri Hartati; Ongko Cahyono (Universitas Sebelas Maret, 2021)
The Assistance of Hybrid Orchid Agribusiness in Matesih District Karanganyar Regency. Matesih District of Karanganyar Regency is known as the center of ornamental plants including orchids. However, most of the farmers grow orchids by raise the juvenile orchids into adult orchids which are then sold. Farmers have not been able to produce seedlings as well as to transfer plantlets from tissue culture bottles to media in pots. These community service programs aim to provide knowledge and increase the skills of partner farmers in acclimatizing hybrid orchids. Therefore they can transfer orchid seeds with a high success rate and earn higher profits from their orchid agribusiness. The program was carried out in Plosorejo Village, Matesih District, Karanganyar Regency from April to October 2020. Partner farmers consist of two farmer groups, namely the farmer group of RT 002 RW XIII and Tani Rejo IX. This program has succeeded in increasing the knowledge and skills of partner farmers in acclimatizing hybrid orchids. In terms of business, this program is profitable because based on the calculation with a capital of Rp869.000, 00 generates a profit of Rp1.311.000,00 per four months with a BC ratio of 1.5.